Challenges of user data privacy in self-sovereign identity verifiable credentials for autonomous building access during the COVID-19 pandemic - Naicker, Denver; Moodley, Mackaylan (Frontiers in Blockchain, 2024)
Self-Sovereign Identity is an emerging field along-side development of blockchain technology. It's use cases are primarily surrounding identity and credential management advocating the privacy of user details during the verification process. Our endeavour was to test and implement the features promoted for Self-Sovereign Identity through open and closed source frameworks utilizing a scenario of building access management to adhere to health risk and safety questionnaires during the Covid-19 pandemic. Our investigation identifies whether user data privacy could be ensured through verifiable credentials and identifies whether business practices would need to evolve to mitigate storing personal data in a centralized manner.